Stakeholder Engagement Strategies for Accelerating Stunting Reduction in Mojokerto: Pathways to Achieving Sustainable Development Goals - Sentanu, I Gede Eko Putra Sri; Ferdiansyah, Muhammad Reynaldi; Adi, Muhammad Wahyu Prasetyo; Arsy, Selma Kendida; Naufal, Muhammad; Wijayanto, Denis; Andini, Athiyyah Putri (Journal of Governance, 2025)
The Mojokerto City Government's sustained efforts in addressing stunting have garnered significant national recognition, evidenced by its receipt of the Innovative Government Award for two consecutive years. These achievements have stimulated scholarly interest in examining the stakeholders involved in these initiatives. The overarching objective is to develop a replicable framework for other regional and municipal governments, fostering broader efforts to combat stunting in Indonesia. This research is grounded in the stakeholder analysis model advanced by Reed et al. (2009), which facilitates the systematic identification, categorization, and analysis of stakeholder relationships. The study adopts a descriptive case study methodology within a qualitative research paradigm, utilizing participatory observation, semi-structured interviews, and document analysis as primary data collection techniques. The findings highlight the involvement of 27 stakeholders in Mojokerto City's stunting reduction programs, categorized into three groups: 4 primary stakeholders, 18 key stakeholders, and five secondaries. Further analysis reveals that stakeholders can also be classified based on their level of interest and influence in achieving the initiatives' goals. Specifically, five stakeholders are identified as key players, nine as subjects, 10 as context setters, and three as crowd members. However, the study also identifies challenges, particularly conflicts arising from community-level misunderstandings of stunting's impacts and the limitations in disseminating critical information effectively. This research underscores the importance of stakeholder collaboration and highlights the need for effective communication strategies to address conflicts and enhance community understanding of stunting prevention efforts.